The Effectiveness of Existential Counseling in Improving Spiritual Intelligence and Perceived Self Efficacy among Breast Cancer Patients in Jordan - Oweidah, Shaima'; Hamdi, Mohammed (Jordan Journal of Educational Sciences, 2015)
The purpose of this study was to develop a group counseling program based on existential counseling for breast cancer women patients, and to investigate its effect on spiritual intelligence (SQ) and perceived self efficacy (PSE).The sample of this study consisted of 24 breast cancer patients, divided randomly into two groups; Experimental group of (12) breast cancer women exposed to existential group counseling program, and control group of (12) breast cancer women who were not exposed to any intervention. Two scales were used in this study: the spiritual intelligence scale and the perceived self efficacy scale. The results of this study showed that there was no significant difference between the two groups in PSE level, and there was significant difference between the two groups in favor of the experimental group in the total score of SQ and in the transcendence domain, which indicates the effectiveness of existential counseling in improving SQ level among breast cancer patients